2020
DOI: 10.1111/pce.13850
|View full text |Cite
|
Sign up to set email alerts
|

Physiological significance of pedospheric nitric oxide for root growth, development and organismic interactions

Abstract: Nitric oxide (NO) is essential for plant growth and development, as well as interactions with abiotic and biotic environments. Its importance for multiple functions in plants means that tight regulation of NO concentrations is required. This is of particular significance in roots, where NO signalling is involved in processes, such as root growth, lateral root formation, nutrient acquisition, heavy metal homeostasis, symbiotic nitrogen fixation and root–mycorrhizal fungi interactions. The NO signal can also be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 228 publications
(272 reference statements)
0
5
0
Order By: Relevance
“…NO has also been extensively proven to be involved in root development [ 8 , 34 , 35 ]. Previous investigations reported that the application of NO donors to different plant species roots promotes the formation of adventitious and lateral roots, root hair development, and root tip elongation, emphasizing the function of NO in root organogenesis [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO has also been extensively proven to be involved in root development [ 8 , 34 , 35 ]. Previous investigations reported that the application of NO donors to different plant species roots promotes the formation of adventitious and lateral roots, root hair development, and root tip elongation, emphasizing the function of NO in root organogenesis [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In plants, nitric oxide (NO) is known as a small but important multifunctional bioactive signaling molecule and plays a critical function as a regulator of plant growth and development, including germination [ 7 ], root growth [ 8 ], flowering [ 9 ], and senescence [ 10 ]. Besides its function in the regulation of plant developmental processes, NO has been found to regulate plant response to stresses caused by heavy metal toxicity [ 11 , 12 ], water deficit [ 13 , 14 ], low-light intensity [ 15 ], salt stress [ 16 ], paraquat toxicity [ 17 ], and plant pathogen [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…RNS is the second most significant messenger after ROS, and its component nitric oxide (NO) is a momentous endogenous molecule of signal that can scavenge ROS directly or induce the antioxidant defense system to scavenge ROS in vivo [39]. Under heavy metal stress, the donor of NO is a single nucleotide polymorphism marker (SNP), which significantly increases the activity of antioxidant enzymes such as SOD, CAT, ascorbate peroxidase (APX), and GST [40], and enhances the content of indole-3-acetic acid (IAA) and gibberellin (GA), resulting in the reduction in ROS production and heavy metal toxicity [41]. Figure 1 shows the mechanisms of heavy metal tolerance in energy crops.…”
Section: Mechanisms Of Heavy Metal Tolerance In Energy Cropsmentioning
confidence: 99%
“…Nitric oxide (NO) plays a versatile role in plant growth and development, including the roots [ 33 ]. For example, the NO signal, leading to decreased cell division and promoted cell differentiation in root meristems, is accumulated by abiotic stimuli, such as salt stress [ 34 ].…”
Section: Developmental Plasticity Via the Primary Apical Meristems Un...mentioning
confidence: 99%